Spiritual dryness and its predictors in Iranian Muslims - Ashrafizadeh, Hadis (Spiritual care, 2024)
Illness, disability, and life-threatening events rank among the most significant crises that give rise to spiritual challenges. These challenges can lead to a dichotomy of spiritual dryness and cohesion, a phenomenon that can manifest in any demographic group due to illness or other crises. Within the Iranian Muslim community, various groups - healthy and sick, religious and non-religious - have consistently experienced spiritual dryness. This observation aligns with findings from other studies, particularly those involving Christians. However, the factors predicting spiritual dryness in these individuals have differed from those in other populations. Given that spirituality often serves as a potent strategy for navigating life's crises, it is crucial to provide holistic support and spiritual care to those grappling with this phenomenon. This approach can help mitigate negative outcomes and foster positive ones, such as post-traumatic growth.